Patients’ perception of quality of anti-retroviral therapy services in south west Nigeria: a cross sectional study - Oyebade, Akin; Familusi, Ishola; Dauda, Olawale (International Journal Of Community Medicine And Public Health, 2022)
Background: The World Health Organization reports that 60% of deaths from conditions requiring health care are due to poor quality of health care in low- and medium-income countries. The aim of this study is to assess quality of antiretroviral therapy (ART) services in Osun State, Nigeria. Methods: This study utilized descriptive cross sectional study design. A semi-structured interviewer-administered questionnaire was developed to collect data from 150 patients receiving ART care from two health facilities providing ART services Results: The mean score for perceived quality of ART care providers was 29.6 with 98.7% of respondents having high score and the mean score for perceived quality of ART Service Delivery was 56.3 with 97.3% of respondents having high score while the mean score for perceived quality of Health Facility structure was 22.1 with 79.3% of respondents having high score. Also, 96.7% of respondents strongly agreed that ART services are satisfactory; however only 22.7% of respondents strongly agreed that time spent with staff was adequate while 62.7% of respondents reported that Medical Records unit had the most delay. Age of respondents and the type of health facility were statistically significantly associated with perception of good quality of care Conclusions: The time spent by patients with ART care providers needs to be optimized and the delay encountered in medical records unit should be reduced to improve quality of ART service delivery. Also, quality of ART care providers in University of Osun teaching hospital and ART facility structure at State Hospital Asubiaro should be improved.